2010
DOI: 10.1111/j.1468-1293.2009.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Yoga lifestyle intervention reduces blood pressure in HIV‐infected adults with cardiovascular disease risk factors*

Abstract: People living with human immunodeficiency virus infection (HIV) are at increased risk for developing cardiovascular disease (CVD). Safe and effective interventions for lowering CVD risk in HIV are high priorities.Objective-We conducted a prospective, randomized, controlled study to evaluate whether a yoga lifestyle intervention improves CVD risk factors, virologic or immunologic status, or quality of life in HIV-infected adults more than in a matched control group.Methods-Sixty HIV-infected adults with mild-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 38 publications
5
85
0
1
Order By: Relevance
“…Two small randomized studies of hatha yoga-type practices evaluated BP as an outcome since 2007. 60,61 A third small trial assessed the impact of a variation of pranayama on a background of hatha yoga practice. In a randomized, controlled clinical trial, yoga-naïve adults with stage I hypertension were randomized to 12 weeks of Iyengar yoga or control arms (enhanced usual care emphasizing diet).…”
Section: Recent Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two small randomized studies of hatha yoga-type practices evaluated BP as an outcome since 2007. 60,61 A third small trial assessed the impact of a variation of pranayama on a background of hatha yoga practice. In a randomized, controlled clinical trial, yoga-naïve adults with stage I hypertension were randomized to 12 weeks of Iyengar yoga or control arms (enhanced usual care emphasizing diet).…”
Section: Recent Trialsmentioning
confidence: 99%
“…61 Baseline and week 20 measures included BP and 2-hour oral glucose tolerance testing with insulin monitoring, body composition, fasting serum lipid/lipoprotein profile, and quality-of-life measures. Resting systolic and diastolic BP levels improved more (P=0.04) in the yoga group (−5±2 and −3±1 mm Hg, respectively) than in the standard of care group (1±2 and 2±2 mm Hg, respectively) without improvement in other measures noted.…”
Section: Recent Trialsmentioning
confidence: 99%
“…Therefore, some studies showed that sport modalities such as Tai Chi Chuan, are efficient in promoting pEH 10 and improving the regulation of the vagal reflex and sensitivity o the baroreflex after some training weeks 24 . Moreover, another modality as yoga may promote Bp reduction in subjects with risk for cardiovascular disease after a training period 25 , despite being a low-intensity physical activity, which is a point in favor of the exercise psychobiological influence on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies indicate that weight, or more specifically BMI, may be reduced in response to MM practices (Cade et al, 2010; Liu et al, 2010; Manchanda et al, 2000), particularly for those who are overweight or obese (Chen et al, 2010), even when compared to non-MM exercise controls (Chen et al, 2010; Cheung et al, 2005; Dechamps et al, 2009). …”
Section: Weight Loss For Bcssmentioning
confidence: 99%